Development of pico-satellite : monopole antenna design - Eng, Si Teng (2010)
In picosatellites, significant fraction of mass, volume, and majority of its power are consumed by the communication subsystems. Hence, the design of the communication subsystems is vital to the overall satellite and mission plans.